PROMOTION OF PURPOSEFUL BEHAVIOR FOR PUPILS WITH BEHAVIORAL DISORDERS IN INCLUSIVE ENVIRONMENT OF PRIMARY SCHOOL - Mutule, Marita (Education Reform: Education Content Research and Implementation Problems, 2019)
Every school year adaptation becomes harder for more and more pupils. Latest scientific research has found that inability to adapt is based on behavioral disorders which have raised the authors' focus on behavioral problems and manifestations in the educational process and their correction in inclusive settings. Children with behavioral disorders have difficulty in self-regulation and social interaction with peers or adults. It is difficult for the pupil to manage, observe, identify and evaluate his / her behavior in different circumstances, environments. For teachers, it becomes harder to teach these pupils. This is why, the aim of the study was to develop a program of purposeful behavior’s promotion that is theory and practice-based.In the theoretical part of the study, the literature of behavioral disorders in primary school and their peculiarities were researched, the problems of behavioral disorders and their ways of expression during the educational process were analyzed and options of purposeful behavior’s promotion in inclusive environment were offered.In the empirical part of the study, a research of the options of purposeful behavior’s promotion for pupils with behavioral disorders in inclusive environment of primary school was made by using the program of purposeful behavior’s promotion created by the author.As a result of the study a learning tool that contains 12 lessons and 43 activities called “Program of purposeful behavior’s promotion for pupils with behavioral disorders in inclusive environment of primary school” was created.The hypothesis of study confirmed - it was found that the indicators of the pupils’ behavior improved if in the inclusive environment the program of purposeful behavior’s promotion was being used.